Usability Testing of Industrial Engineering UPNVJT Website Using Eye Tracking and System Usability Scale - Bintara Putra Dicya; Tranggono (Sinkron : jurnal dan penelitian teknik informatika, 2024)
Websites are essential for agencies and organizations to ensure their information is accessible to the public. The eye tracker method is effective for evaluating user usability. The Industrial Engineering Study Program at Universitas Pembangunan Nasional "Veteran" East Java has an official website, tekindustri.upnjatim.ac.id, which has not been tested for usability. Initial problem identification revealed issues such as inaccessible menus and hidden information. This study aims to assess and improve the user experience on the website using a combination of Eye Tracking and System Usability Scale (SUS) methods. The average effectiveness score for 39 respondents is 89.10%, with 8% rated as ineffective, 28% as effective enough, and 64% as very effective. The efficiency value, measured across 39 respondents and 4 tasks, is 0.0276 goals/second, indicating each respondent completes 2.76% of tasks per second, requiring about 36.23 seconds to reach 100% task completion. The initial SUS score was 69.49%. Five issues were identified in the Home, Facilities, Education, Thesis, and MBKM sections and one design issue. A prototype was developed and tested, resulting in a final SUS score of 80.06%, placing the website in the marginally high acceptability range, category B for grade scale, and excellent for adjective ratings. The SUS score improvement was 10.57%. This research shows that combining Eye Tracking and SUS is an effective method for increasing website usability. The implications of this research can help organizations improve the quality of their websites and provide a better user experience.